Study on Influence on Sensitive of Thermosensitive Element to Open Jet Angular Velocity Sensor - Wang, Yuxin; Piao, Linhua; Li, Bei (2019 IEEE 4th Advanced Information Technology, Electronic and Automation Control Conference (IAEAC), 2019)
The mechanism of the influence of the setting of the thermal sensor on the sensitivity of the open jet angular velocity sensor is explained. Using the fluid-solid coupling method, the distribution of gas velocity at different input angular velocities at the thermosensitive element in the sensor is calculated. The calculation results show that when the angular velocity is input around Z axis, the distance d=0.6mm between the thermistor wires can reduce the influence of eddy current in the jet sensitive chamber, increase the temperature change of the thermistor wires, thus increase the output voltage of Wheatstone bridge, and improve the sensitivity of the open jet angular velocity sensor.